2007
DOI: 10.1016/j.jembe.2007.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrata and conspecific odour on the metamorphosis of mangrove crab megalopae, Ucides cordatus (Ocypodidae)

Abstract: Environmental cues associated with the adult habitat induce metamorphosis in many marine invertebrate larvae and thus settlement in a place appropriate for completing their life-cycle. Ucides cordatus is a semi-terrestrial crab that exemplifies organisms living in mangrove estuaries as adults, but whose larvae develop offshore and return to the estuarine environment prior to metamorphosis. We investigated the influence of substrata (burrow mud, channel-bank mud, dead wood, sand, nylon mesh) and conspecific adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Recent laboratory experiments showed that chemical cues emitted by conspecific crabs, regardless of gender, enhance the survivorship and induce the settlement of U. cordatus megalopae (DIELE & SIMITH 2007, SIMITH & DIELE 2008. As U. cordatus odour concentrations are likely to be higher inside conspecific burrows than outside, settlement may indeed occur more frequently (or exclusively?)…”
mentioning
confidence: 99%
“…Recent laboratory experiments showed that chemical cues emitted by conspecific crabs, regardless of gender, enhance the survivorship and induce the settlement of U. cordatus megalopae (DIELE & SIMITH 2007, SIMITH & DIELE 2008. As U. cordatus odour concentrations are likely to be higher inside conspecific burrows than outside, settlement may indeed occur more frequently (or exclusively?)…”
mentioning
confidence: 99%
“…Conspecific cues enhance settlement and metamorphosis (Forward et al 2001, Diele & Simith 2007, while predator cues generally reduce metamorphosis or accentuate habitat choices (Moksnes et al 1997, Welch et al 1997. If the juvenile cue treatment was perceived as conspecifics, we would have expected settler distributions to remain even among habitat types.…”
Section: Preferencementioning
confidence: 99%
“…These may be related to the patchy distribution of microhabitats, small-scale changes in environmental conditions, behavior and competition. For example, habitat choice and recruitment of U. cordatus megalopae are strongly induced by environmental cues associated with the presence of conspeciWc crabs and muddy sediments (Diele and Simith 2007), which is likely to be more important in regulating patterns of distribution at small scales. Other small-scale processes, such as intraspeciWc competition, may explain the diVerences in the spatial patterns of non-commercial and commercial size crabs, since large crabs apparently exclude smaller ones from preferred habitats (Piou et al 2009).…”
Section: Crab Burrows < 60 MMmentioning
confidence: 99%